Combined effects of grazing management and climate on semi‐arid steppes: Hysteresis dynamics prevent recovery of degraded rangelands. Issue 9 (24th July 2019) - Cipriotti, Pablo A.; Aguiar, Martín R.; Wiegand, Thorsten; Paruelo, José M.
Abstract: Livestock grazing has degraded many arid and semi‐arid rangelands around the world, and the drier climate predicted by climate change scenarios may amplify these effects and even lead to catastrophic vegetation shifts. We assess the long‐term effects (1900–2100) of grazing and rainfall on various aspects of vegetation structure including the grass‐shrub balance, the maintenance of spatial vegetation patterns, and the decline or recovery of palatable grasses (e.g. Poa ligularis ) on a cover and/or density basis. We used the eco‐hydrological and individual‐based simulation model DINVEG for this purpose, which describes the spatiotemporal dynamics of Patagonian grass‐shrub steppes based on six decades of field research (1955–2018). Rainfall and grazing affected the simulated vegetation structure in different ways. Total plant cover was mostly influenced by rainfall, but the cover of palatable grasses was mostly influenced by stocking rate. Dry conditions and low stocking rates (122 mm/year and <0.2 sheep/ha) favoured grasses over shrubs, whereas shrub encroachment occurred only in the high rainfall scenario combined with high stocking rates (181 mm/year and >0.2 sheep/ha). High stocking rates and/or drier conditions caused only gradual shifts in spatial vegetation patterns, but maintained the observed positive association for grasses around shrubs. In contrast, shrub encroachment was associated with repulsion between grasses and shrubs and the formation of shrub clusters into a matrix of scattered less palatable grasses. Plant compositional changes occurred through grass species replacement (e.g. P. ligularis is replaced by Pappostipa humilis ) and the associated hysteresis effect of palatable grass species: model simulations suggest that 2–3 decades of heavy and year‐long continuous grazing can drive palatable grasses to close to extinction, whereas natural recovery of degraded steppes may take 100 years or longer. Synthesis and applications . Desertification and climate change challenge grazing management in semi‐arid rangelands, especially in already degraded ecosystems. Management that alternates between years of grazing and resting was effective to maintain the cover of palatable grasses, but this allowed for only very slow recovery of degraded steppes. While drier climate and grazing may not change the overall spatial patterns of vegetation, our results are rather pessimistic regarding the short‐term recovery of palatable grasses. This will require increasing complexity in ecosystem restoration efforts, combined with interventions such as sowing, watering, reseeding or major changes in land use. Abstract : Desertification and climate change challenge grazing management in semi‐arid rangelands, especially in already degraded ecosystems. Management that alternates between years of grazing and resting was effective to maintain the cover of palatable grasses, but this allowed for only very slow recovery of degraded steppes. While drier climate and grazing may not change the overall spatial patterns of vegetation, our results are rather pessimistic regarding the short‐term recovery of palatable grasses. This will require increasing complexity in ecosystem restoration efforts, combined with interventions such as sowing, watering, reseeding or major changes in land use. Resumen: El pastoreo doméstico ha degradado muchos pastizales áridos y semiáridos en todo el mundo, y el clima más seco predicho por los escenarios de cambio climático puede amplificar estos efectos e incluso conducir a cambios catastróficos en la vegetación. Evaluamos los efectos a largo plazo (1900–2100) del pastoreo y de la lluvia para varios aspectos de la estructura de la vegetación, incluyendo el balance entre pastos y arbustos, el mantenimiento de los patrones espaciales y la disminución o recuperación de pastos palatables (e.g. Poa ligularis ) en base a cambios en la cobertura y/o densidad. Para ello se utilizó el modelo de simulación eco‐hidrológico basado en individuos DINVEG, que describe la dinámica espacio temporal de las estepas graminoso‐arbustivas de la Patagonia en base a seis décadas de investigación de campo (1955–2018). Las precipitaciones y el pastoreo afectaron la estructura de la vegetación simulada en modos distintos. La cobertura total estuvo influenciada principalmente por las lluvias, pero la cobertura de pastos palatables fue influenciada principalmente por la carga ganadera. El escenario climático seco y la baja carga ganadera (122 mm/año y < 0, 2 ovejas·ha ‐1 ) favorecieron a los pastos frente a los arbustos, mientras que la invasión de arbustos solo se produjo en el escenario húmedo combinado con altas cargas ganaderas (181 mm/año y > 0, 2 ovejas·ha ‐1 ). Las altas cargas ganaderas y/o las condiciones secas causaron sólo cambios graduales en los patrones espaciales de la vegetación, pero mantuvieron las asociaciones positivas de los pastos alrededor de los arbustos. En cambio, la invasión de arbustos se asoció con la repulsión entre pastos y arbustos y la formación de isletas de arbustos en una matriz de pastos no palatables esparcidos. Los cambios en la composición florística se produjeron a través del reemplazo de especies de gramíneas (e.g. P. ligularis es reemplazada por Pappostipa humilis ) y el efecto de histéresis observado en las especies de pastos palatables: las simulaciones sugieren que 2–3 décadas de pastoreo con altas cargas durante todo el año pueden llevar a los pastos palatables a una situación cercana a la extinción, mientras que la recuperación natural de las estepas degradadas puede llevar 100 años o más. Síntesis y aplicaciones . La desertificación y el cambio climático desafían al manejo del pastoreo en los pastizales semiáridos, especialmente en ecosistemas ya degradados. El manejo rotativo del pastoreo donde alternan períodos de descanso fue efectivo para mantener la cobertura de pastos palatables, pero sólo permitió una recuperación muy lenta de las estepas degradadas. Mientras que el clima seco y el pastoreo pueden no cambiar los patrones espaciales generales de la vegetación, nuestros resultados son bastante pesimistas con respecto a la recuperación a corto plazo de los pastos palatables. Esto requerirá de esfuerzos más complejos para la restauración de estos ecosistemas, combinados con intervenciones como la siembra, el riego, la resiembra o cambios drásticos en el uso de la tierra.